Evidence for necrosis, but not apoptosis, in human hepatoma cells with knockdown of mitochondrial aquaporin-8 - Marchissio, Maria Julia (2014)
We previously found that mitochondrial aquaporin-8 (mtAQP8) channels facilitate mitochondrial H2O2 release in human hepatoma HepG2 cells and that their knockdown causes oxidant-induced mitochondrial dysfunction and loss of viability. Here, we studied whether apoptosis or necrosis is involved as the mode of cell death. We confirmed that siRNA-induced mtAQP8 knockdown significantly decreased HepG2 viability by MTT assay, LDH leakage, and trypan blue exclusion test. Analysis of mitochondrial proapoptotic Bax-to-antiapoptotic BclXL ratio, mitochondrial cytochrome c release and caspase-3 activation showed no alterations in mtAQP8-knockdown cells. This indicates a primary mechanism of cell death other than the intrinsic mitochondrial apoptotic pathway. Thus, nuclear staining with DAPI did not reveal any increase of apoptotic features, i.e. chromatin condensation or nuclear fragmentation. Flow cytometry studies after double cell staining with annexin V and propidium iodide confirmed lack of apoptosis and suggested necrosis as the primary mechanism of death in mtAQP8-knockdown HepG2 cells. Necrosis was further supported by the increased nuclear delocalization and extracellular release of the High Mobility Group Box 1 protein. The knockdown of mtAQP8 in another human hepatoma-derived cell line, i.e. HuH-7 cells, also induced necrotic but not apoptotic death. Our data suggest that mtAQP8 knockdown induces necrotic cell death in human neoplastic hepatic cells, a finding that might be relevant to therapeutic strategies against hepatoma cells.